Pengelolaan arsip dinamis (surat masuk dan surat keluar) di Universitas Indo Global Mandiri - Ramdani ramadani (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2018)
This article discusses the Management of incoming and outgoing Dynamic Archives letters at the University of Indo Global Mandiri. In this article, we discuss the importance of competent human resources in the field of filing, namely those who are experts in filing. The data collection techniques we use are deeper approach interview techniques and focus group discussions. Management of dynamic records of incoming and outgoing mail is all forms of archiving that are temporary in nature because only the temporary need is different if it is important because it involves the law and legality of an institution. Regarding the dynamic processing of incoming mail and mailing out using the Manual is very good. But along with the changing times are increasingly advanced. Any manual work will be abandoned. Keywords: Dynamic archives, management of incoming and outgoing mail, college archives.